Maximum oxygen uptake and sexual maturity of children and adolescents - Roberto Jerônimo dos Santos Silva; Édio Luiz Petroski (Desafio Singular, 2008)
The objective of this study was to analyze the maximum oxygen uptake of children and adolescents during puberty. The study enrolled 779 children and adolescents of both sexes from Cotinguiba, SE, Brazil, 404 of whom were female and 379 of whom were male. Measurements were taken of weight, height and skin folds. Body fat percentage and lean body mass. Sexual maturity stages were established by self-assessment, based on appearance of pubic hair. The children's VO2max was estimated from the results of a 20 meter shuttle-run test. Data analysis employed descriptive statistics, Pearson's correlation coefficient and analysis of variance (p²0.05). The results suggest that absolute VO2max (l/min) increases progressively in both sexes as maturity advances. Significant differences between sexes are observed from maturity stage P3 onwards. Correlations between absolute VO2max (l/min) and maturity stages were significant for both sexes (p<0.05); while correlations between VO2max (relative to body weight and lean body mass), were negative for females (p<0.05). Analyses suggest that during puberty absolute VO2max increases gradually for both sexes, that VO2max is stable with relation to body mass, and that lean mass in males and decreases in females as sexual maturity advances.